Four new species of Neischnocolus (Araneae: Mygalomorphae: Theraphosidae) from Western Ecuador - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2025)
Four new species of the small mygalomorph genus Neischnocolus (Theraphosidae) are described from Western Ecuador: N. ballerioi sp. nov. (male); N. pampenita sp. nov. (male, female); N. ruffoi sp. nov. (male, female) and, N. canosita sp. nov. (male). Additionally, the female of Neischnocolus cisnerosi Peñaherrera et al. 2023 is described for the first time.